Sworn virgin - Bispuri, Laura 1977-; Rohrwacher, Alba 1979-; Kodheli, Flonja; Eidinger, Lars 1976-; Manieri, Francesca 1979- (Strand Releasin, 2016)
A young woman named Hana who lives in an Albanian village ruled by men, takes an oath of eternal virginity to live as a sworn virgin, becoming Mark, so she can live free as a man. Years later, restless and feeling imprisoned by his choice, Mark leaves for Italy to visit his sister and family. There, he explores the unexpected pleasures of attraction and the body and decides to abandon Mark, rediscovering herself/himself as Hana, to become a new and liberated person
Original: 2015
Farbe, Bildformat: widescreen
Keywords: Sex role / Albania / Drama; Male impersonators / Albania / Drama; Sisters / Albania / Drama; Frau; Albania / Women / Social conditions / Drama; Film; DVD-Video